Appraisal of the Occupation and Wage Status of Brick Factory Workers in Chandragiri Municipality, Kathmandu (Saptagandaki Journal, 2023)
The brick factories are manufacturing industries which apply labour intensive techniques. Workers in a large number have been involved in the brick factories but their occupation and wage status is unknown. The authorized government agencies have shown less concern to this aspect of the workers. To this backdrop, the present study was conducted to investigate the occupational load and wage status of the workers in brick factories. The study made use of descriptive research design, collecting primary data. The data were collected adopting interview and observation techniques. The analysis of data revealed that the brick factories involved under-aged workers and provided low wages. They have employed unskilled workforces on part time basis for long periods of time in low wages as compared minimum wage announced by Nepal Government and International Labour Organization (ILO). For instance, they provided only Rs. 330 per day for carrying the load of 1000 bricks. About ninety seven percent of labors were involved as part-time job holders working only six months in a year and only three percent of labors were found working as full-time job holders.